Voices from the Forest: Indigenous Perspectives on Conservation and Cultural Identity in Southeast Asia - Ahmad Jamaludin Jambunanda; Muhammad Amin Musa; Karimuddin Karimuddin; Lamin Jassey; Dalilatul Muparikhah (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This article examines the critical role of Indigenous Peoples in Southeast Asia in both nature conservation and cultural preservation. Employing a qualitative methodological approach, this study incorporates case studies from Indonesia, Malaysia, and Vietnam. Data collection was conducted through literature reviews of reputable sources and interviews with indigenous community members. The findings highlight the unique knowledge and traditions Indigenous Peoples uphold in sustaining cultural and environmental heritage. However, they encounter a range of challenges, including land disputes, the adverse effects of climate change, and systemic discrimination against unrecognised indigenous rights. This article seeks to articulate the key arguments and contributions of research in advocating for the legal protection and recognition of Indigenous Peoples’ rights, while also examining the role of mass media in fostering public awareness of their struggles. It is anticipated that the findings of this study will serve as a foundation for formulating policies that more effectively support the sustainability of both indigenous communities and their environment.